Respuestas

2012-10-01T04:10:23+02:00

Si esto es un sistema de ecuaciones

 

entonces las soluciones para 5x^2+5y^2=12  y 3x^2-2y^2=6

 

tenemos las siguiente soluciones

 

x =-\frac{3\sqrt{6}}{5}   y   y =-\frac{\sqrt{6}}{5}

 

x =-\frac{3\sqrt{6}}{5}   y   y =\frac{\sqrt{6}}{5}

 

 

x =\frac{3\sqrt{6}}{5}   y   y =-\frac{\sqrt{6}}{5}

 

x =\frac{3\sqrt{6}}{5}   y   y =\frac{\sqrt{6}}{5}

¡La mejor respuesta!
2012-10-01T04:11:48+02:00

sea:

x^2 = a

y^2 = b

 

entonces tendremos:

1) 5a+5b=12

2) 3a-2b=6

 

1)*2 y 2)*5

10a+10b=24

15a-10b=30

 

sumando:

10a+15a +10b-10b = 24+30

25a = 54

a= 54/25

reemplazando en 1)

 

5a+5b=12

5(54/25)+5b=12

54/5+5b=12

5b= 12-54/5

5b= (60-54)/5

5b=6/5

b=6/25

 

luego

a=x^2=54/25 => x= +/- raiz(54/25)= +/- raiz(54)/5

b=y^2=6/25 => y= +/- raiz(6/25)= +/- raiz(5)/5